2021
DOI: 10.1177/17470218211009159
|View full text |Cite
|
Sign up to set email alerts
|

Adult bilinguals outperform monolinguals in theory of mind

Abstract: Theory of mind (ToM) is an essential ability for social competence and communication, and it is necessary for understanding behaviors that differ from our own (Premack and Woodruff, 1978). Research on bilingual children has reported that 3 and 4-year-old bilinguals outperform monolinguals in ToM tasks. Research suggests that adult bilinguals also might outperform monolinguals (Rubio-Fernandez and Glucksberg, 2012), nevertheless, this effect has yet to be established. Here, we tested bilingual and monolingual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
0
10
1
1
Order By: Relevance
“…Overall, these findings highlight the need to (1) differentiate speakers of two languages from speakers of three or more languages in research on multilingualism and cognition, and (2) make concerted efforts to recruit larger samples of multilingual participants to allow for adequate comparisons between language groups (as suggested by Brysbaert, 2021). The results we observed ran counter to our original theorizing and depart from past demonstrations that bilingualism is associated with a ToM advantage in both children (see Schroeder, 2018 for a meta-analysis) and adults (Navarro & Conway, 2021;Navarro et al, 2022;Rubio-Fernández & Glucksberg, 2012). A great deal of our initial theorizing was rooted in a potential executive functioning advantage for bilinguals.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Overall, these findings highlight the need to (1) differentiate speakers of two languages from speakers of three or more languages in research on multilingualism and cognition, and (2) make concerted efforts to recruit larger samples of multilingual participants to allow for adequate comparisons between language groups (as suggested by Brysbaert, 2021). The results we observed ran counter to our original theorizing and depart from past demonstrations that bilingualism is associated with a ToM advantage in both children (see Schroeder, 2018 for a meta-analysis) and adults (Navarro & Conway, 2021;Navarro et al, 2022;Rubio-Fernández & Glucksberg, 2012). A great deal of our initial theorizing was rooted in a potential executive functioning advantage for bilinguals.…”
Section: Discussioncontrasting
confidence: 93%
“…We examined performance on the RMET, which measures the ability to infer mental states based on subtle nonverbal cues. Previous studies used either the Sally-Anne task (Rubio-Fernández & Glucksberg, 2012) or the director task (Navarro & Conway, 2021;Navarro et al, 2022), which may recruit executive functioning to a greater extent than the RMET. For example, in the director task, participants are required to ignore their own predominant viewpoint and focus on the director's viewpoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enhanced social flexibility (Ikizer & Ramírez-Esparza, 2018) was evidenced by Fan et al (2015) who found that both bilingual and monolingual children situated in a bilingual environment performed better on a mentalizing task than monolingual children who were only exposed to one language (replicated with babies in Liberman et al, 2017). A growing body of work has also shown that personal experiences in bilingualism enhance mentalizing skills across the lifespan (Goetz, 2003; Navarro & Conway, 2021; Rubio-Fernández & Glucksberg, 2012; Schroeder, 2018; Sundaray et al, 2018; Tiv, O’Regan, & Titone, 2021). As mentioned, Tiv, O’Regan, and Titone (2021) tested adult bilinguals in Montréal on a novel mentalizing reading and rating task, finding that bilinguals with greater personal language diversity were more accurate at mentalizing, whereas linguistic coherence was unaffected.…”
Section: What Is Mentalizing?mentioning
confidence: 99%
“…Because some of the grid's compartments are blocked off from the director's view, the participant must take the director's view into account to identify the correct referent objects. Native bilingual children have been found to be more successful in doing so than their monolingual counterparts (Fan et al, 2015; for adults see Navarro & Conway, 2021). Even children who grow up being exposed to a multilingual environment from early on, but without speaking a second language (L2), exhibit advanced performance.…”
Section: Introductionmentioning
confidence: 99%